2019
DOI: 10.1002/jbm.a.36706
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of cell infiltration in an electrospun scaffold with multiple synthetic biodegradable polymers using sacrificial PEO microparticles

Abstract: Electrospinning is a fabrication technique to generate three dimensional scaffolds with a fiber structure that imitates extracellular matrix for tissue engineering constructs. The versatile characteristics of the electrospinning process yields designer scaffolds made of biodegradable polymers or natural proteins with controllable fiber diameters, biodegradation, and mechanical properties. A limitation of conventional electrospun scaffolds is the dense fiber packing with low porosity that leads to poor cell inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…The sacrificial PEO microspheres were incorporated to increase the pore size and porosity of the PGA electrospun scaffold. We have previously reported the porosity of an electrospun PGA scaffold increased from 72% with PGA alone to 90% in a composite scaffold after the removal of the PEO microparticles (Hodge & Quint, 2019). The dimensions of the PGA scaffold were 4.5 mm inner diameter, 8 cm length, and 0.7 mm thickness (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sacrificial PEO microspheres were incorporated to increase the pore size and porosity of the PGA electrospun scaffold. We have previously reported the porosity of an electrospun PGA scaffold increased from 72% with PGA alone to 90% in a composite scaffold after the removal of the PEO microparticles (Hodge & Quint, 2019). The dimensions of the PGA scaffold were 4.5 mm inner diameter, 8 cm length, and 0.7 mm thickness (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…This study showed the feasibility of an electrospun biodegradable PGA scaffold in combination with a biomimetic culture system to generate a functional tissue‐engineered vessel. A potential limitation of electrospun scaffolds is the dense fiber packing that prevents cell infiltration; hence, electrospraying a sacrificial porogen to increase the porosity and pore size significantly enhanced cell infiltration and matrix formation as the PGA degraded in the bioreactor (Hodge & Quint, 2019; Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SA does not have sufficient mechanical stability that, in turn, may result in the formation of a gel with low efficiency and damage its elasticity [18]. To respond to this challenge, cross-linking agents such as polyethylene oxides (PEO) are useful [19,20]. PEO is a crystalline thermoplastic water-soluble polymer with the molecular formula of H-(-O-CH 2 -CH 2 -)n-OH.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is used for the removal of dyes and metals [15,16] as it has active adsorption sites like amino (-NH 2 ) and hydroxyl (-OH) functional groups and metals. However, it has some disadvantages for industrial applications [3], wastewater technologies, such as the too soft structure, which creates problems [17][18][19], its high solubility in the organic solvent, high swelling percent in water, low mechanical strength, and low surface area [20]. Many studies have been applied to improve CS properties and efficiency [21][22][23].…”
Section: Introductionmentioning
confidence: 99%